PENGARUH LOVE OF MONEY DAN MACHIAVELLIAN TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI - Pramudita, Melati Pramudita; Triani, Merry; Fiorintari (Eksos, 2024)
This research aims to determine Love of Money and Machiavellianism on Accounting Students' Ethical Perceptions. Through ethical perception, it can be seen how students, especially accounting students, view violations that occur among accountants with the aim of providing an overview to all prospective accountants regarding the professionalism of an accountant who works based on public trust. This research uses primary data collected using a questionnaire as a data collection instrument which is distributed to respondents. The population in this study were all final semester students in the accounting department of Pontianak State Polytechnic. By using the Solvin formula, the sample for this study was 189 people. The respondents in this research were students majoring in Accounting at the Pontianak State Polytechnic. The data analysis used was SPSS software. The research results show that Love of money has a positive effect on the ethical perceptions of accounting students at the Pontianak State Polytechnic. Machiavellian has a positive influence on the ethical perceptions of accounting students at Pontianak State Polytechnic. Love of money and Machiavellianism simultaneously have a significant influence on the ethical perceptions of accounting students at the Pontianak State Polytechnic accounting department.